Safety of Medical Devices in Poland – Analysis of Withdrawn and Suspended Certificates of Compliance - Patryn, Rafał (Med Devices (Auckl), 2021)
INTRODUCTION: In the European Union, the process of controlling currently used medical devices is carried out and determined by legal provisions. The law stipulates that each entity responsible for using medical equipment must confirm its safety with an appropriate certificate issued by a notifying body. In Poland, the entity responsible for keeping records as to the withdrawn and suspended certificates, is the Office for Registration of Medicinal Products, Medical Devices, and Biocidal Products (URPL). Certification is required for all medical devices prior to their introduction onto the market and during their use. PURPOSE: The article presents data concerning the number of medical devices that failed to meet the certification criteria. METHODS: The research method is an analysis of available subject literature and a report on withdrawn and suspended certificates of medical devices in Poland. RESULTS: In the years 2014–2020, the notified bodies withdrew and suspended 13,354 certificates for medical devices, of which 9792 certificates were withdrawn, 2852 suspended and one falsified. CONCLUSION: The suspension or withdrawal of a certificate for medical devices due to the inefficiency, obsolescence, imprecision, or safety of the devices is an action that improves the safety of patients. Such action reduces the number of medical damages and the obligation to pay compensation to those injured.